Observe and be mindful - Mizusaki, Jorge M (Scientific Journal of the Foot & Ankle, 2019)
The members of ABTPé deserve recognition for the effective and prolific work they produce when the goal is scientific, with emphasis on our professional improvement. The concern about technical and scientific development and improvement of the association’s members is clearly highlighted by the high quality of our presentations. In our country of continental dimensions, we see many different approaches that we can apply to patients in a search for the best solutions for individuals affected by ankle and foot conditions. When evaluating our results, the interest and rights of patients should be considered, and therefore, we must keep in mind the need to accurately plan our routine practices. The care for these individuals should include a wide range of services that promote their psychological and social wellbeing and their working conditions. This is how we view a broader perspective that involves questions reflecting on how our actions affect individuals’ lives. This concern should also address the needs regarding our own quality of life. It thus becomes necessary to identify and focus on the factors that are worth the expenditure of our energy and to act mindfully in the pursuit of rewards for our actions. The diversity of our practice has demonstrated that we will be able to keep pace with technological development and apply it in a way that preserves the greater interest of patients. The format of this care will be very important in light of the enormous variety of disorders that affect the feet, as shown by the number of subjects addressed in this edition. Have a great reading. Act ethically, be mindful. Jorge Mitsuo Mizusaki Editor-in-Chief